Database Principles : fundamentals of design, implementation, and management - Coronel, Carlos; Morris, Steven ;Rob, Peter (Australia : Course Technology Cengage Learning, 2013)
A good textbook. Note that this is not a book on a specific technology, but like most textbooks it explains foundation concepts and tends towards developing trends by the end of the book. As someone who works with databases every day I would say overall the level of the book is beginner to intermediate, with some advanced topics here and there.
PART 1. Database systems -- PART 2. Database Alternatives -- PART 3. Database programming -- PART 4 -- Database Design -- PART 5. Implementation Alternatives -- PART 6. Database Management -- Glossary -- Index.
Includes index.
Keywords: DATABASE DESIGN